2019
DOI: 10.1162/jocn_a_01411
|View full text |Cite
|
Sign up to set email alerts
|

Expected Reward Value and Reward Uncertainty Have Temporally Dissociable Effects on Memory Formation

Abstract: Anticipating rewards has been shown to enhance memory formation. Although substantial evidence implicates dopamine in this behavioral effect, the precise mechanisms remain ambiguous. Because dopamine nuclei have been associated with two distinct physiological signatures of reward prediction, we hypothesized two dissociable effects on memory formation. These two signatures are a phasic dopamine response immediately following a reward cue that encodes its expected value and a sustained, ramping response that has… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 61 publications
(21 reference statements)
11
39
0
Order By: Relevance
“…Moreover, our results support previous studies reporting better memory for information presented in association with feedback, such as positive versus negative feedback 15,16 , larger feedback prediction errors 16,21,33,34 , or the unsigned feedback prediction error 34 . However, some other studies report that memory was not modulated by feedback magnitude 1,21 or feedback prediction error 35 , or was negatively influenced by the feedback prediction error 36 . Unfortunately, these studies, although being just a handful, present a large variety in experimental parameters which may have contributed to these seemingly discrepant results.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Moreover, our results support previous studies reporting better memory for information presented in association with feedback, such as positive versus negative feedback 15,16 , larger feedback prediction errors 16,21,33,34 , or the unsigned feedback prediction error 34 . However, some other studies report that memory was not modulated by feedback magnitude 1,21 or feedback prediction error 35 , or was negatively influenced by the feedback prediction error 36 . Unfortunately, these studies, although being just a handful, present a large variety in experimental parameters which may have contributed to these seemingly discrepant results.…”
Section: Discussionsupporting
confidence: 91%
“…To name a few: encoding type (incidental versus intentional), memory type (associative versus recognition memory), encodingtesting delay period (short versus long), sleep during the delay period (with versus without sleep), task relevance of memoranda, timing of stimuli, and reinforcement learning paradigm (Pavlovian versus instrumental). While the potential influence of these factors on reward-related memory have been discussed elsewhere 16,35 , we note that many of the studies reporting a positive impact of feedback value on memory formation (including ours), presented the information to be remembered (i.e., the memoranda) in close temporal vicinity to the feedback 16,21,33,34 , while those reporting no or a negative impact of feedback value presented the memoranda prior to the feedback 35,36 . For example, Jang et al 35 presented rewards either before memoranda (to induce reward anticipation), during memoranda (to elicit what the authors termed an "image prediction error"), or after memoranda (to elicit a feedback prediction error).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Consistent with this account, reward-related memory benefits are most commonly observed in studies using delayed testing (e.g., 24 h) (Adcock, Thangavel, Whitfield-Gabrieli, Knutson, & Gabrieli, 2006;Murty, Tompary, Adcock, & Davachi, 2017;Wittmann et al, 2005). While immediate memory benefits have also been observed (Gruber, Ritchey, Wang, Doss, & Ranganath, 2016;Gruber, Watrous, Ekstrom, Ranganath, & Otten, 2013;Murty & Adcock, 2014), studies explicitly comparing across delay intervals have often observed memory benefits for delayed testing but not for immediate testing, suggesting that reward enhancement of memory may be more strongly dependent on consolidation processes (Murayama & Kitagami, 2014;Patil, Murty, Dunsmoor, Phelps, & Davachi, 2017;Stanek, Dickerson, Chiew, Clement, & Adcock, 2018;Wittmann et al, 2005).…”
Section: Reward Motivation Enhances Attentional Preparation and Impromentioning
confidence: 83%